The role of mesophases in the ordering of polymers. (August 2016) - Pérez, E.; Cerrada, M.L.; García-Peñas, A.; Gómez-Elvira, J.M.; Fernández-Blázquez, J.P.; Martínez-Gómez, A.; López-Velázquez, D.; Martínez, J.C.
Graphical abstract: Highlights: The role of different kinds of mesophases in the ordering of polymers is analyzed. Variable temperature synchrotron X-ray diffraction experiments are mainly employed. The solid mesophases are found to be competitors with the 3D crystal phases. Liquid crystalline mesophases are precursors of the eventual crystallization. In some cases, mesophase and amorphous profiles are difficult to differentiate. Abstract: The role played by mesophases in the ordering of polymers, namely if they are either competitors with the more stable crystal structures, or they act as precursors of subsequent crystallization, has been analyzed in two kinds of systems: (a) isotactic polypropylene and copolymers with 1-pentene, as representative of forming solid mesophases, and (b) liquid crystalline polymers with biphenyl mesogens (polybibenzoates and esters of hydroxypropylcellulose with different acids including the biphenyl group). Variable-temperature synchrotron experiments have been the primary tool in order to evaluate the formation and stability of those mesophases as function of composition, chemical structure and crystallization conditions (mainly the cooling rate). The results show, in the first case, that the mesophase forming rate depends strongly on comonomer content, and that these solid mesophases are really competitors with the 3D phases. Additionally, a rather complicated polymorphic behavior is exhibited by the 1-pentene copolymers at intermediate contents, where the mesophase is a competitor with both trigonal and monoclinic crystals. On the contrary, in the case of liquid crystalline mesophases these are precursors of the eventual subsequent crystallization. Moreover, correlation lengths and phase behavior in hydroxypropylcellulose esters were found to depend strongly on the degree of substitution, in such a way that differentiation between the mesophase and the isotropic amorphous profile becomes increasingly difficult.